On the Methodological Controls for Determining the Meanings of Words: A Reading in Some the Dictionaries of Ghareeb Al-Hadeeth - delmadji, abdelkader (LANGUAGE ART, 2025)
The issue of determining the meaning of words is one of the issues that has been the focus of attention of linguists in general and lexicographers in particular, and there are many opinions about the methodological bases adopted in determining and controlling the meaning of words in their various contexts. After all, meaning is the most important requirement for the user of the lexicon. Hence, recent studies have called for re-reading the lexical heritage with the aim of upgrading and developing it; perhaps one of the most prominent things that can be upgraded and developed in reading the dictionaries of Ghareeb al-Hadeeth al-Nabawi is to benefit from those methodological controls established by the modernists to determine the meanings of vocabulary in a way that contributes to presenting them free from ambiguity and confusion and close to access and achievement, enabling the realization of the purposes of religious discourse represented in the texts of the Prophetic Hadith and the development of language use skills - among its recipients - in the correct and correct aspects of the correct and correct aspects of the Faceeh. In this paper, we would like to present a reading of the dictionaries of the strangeness of the Prophet’s hadith in order to explore the methodological controls that can be included in them to determine the meanings of vocabulary in the light of comparing them with the findings of modern lexicographers.